Plasmids of Psychrotolerant Polaromonas spp. Isolated From Arctic and Antarctic Glaciers – Diversity and Role in Adaptation to Polar Environments - Ciok, Anna; Budzik, Karol; Zdanowski, Marek K.; Gawor, Jan; Grzesiak, Jakub; Decewicz, Przemyslaw; Gromadka, Robert; Bartosik, Dariusz; Dziewit, Lukasz (Frontiers in Microbiology, 2018)
Cold-active bacteria of the genus Polaromonas (class Betaproteobacteria) are important components of glacial microbiomes. In this study, extrachromosomal replicons of 26 psychrotolerant Polaromonas strains, isolated from Arctic and Antarctic glaciers, were identified, sequenced and characterized. The plasmidome of these strains consists of 13 replicons, ranging in size from 3,378 to 101,077 bp. In silico sequence analyses identified the conserved backbones of these plasmids, composed of genes required for plasmid replication, stable maintenance and conjugal transfer. Host range analysis revealed that all of the identified plasmids are narrow-host-range replicons, only able to replicate in bacteria of closely related genera (Polaromonas and Variovorax) of the Comamonadaceae family. Special attention was paid to the identification of plasmid auxiliary genetic information, which may contribute to the adaptation of bacteria to environmental conditions occurring in glaciers. Detailed analysis revealed the presence of genes encoding enzymes potentially involved in (i) protection against reactive oxygen species, ultraviolet radiation and low temperatures, (ii) transport and metabolism of organic compounds, (iii) transport of metal ions and (iv) resistance to heavy metals. Some of the plasmids also carry genes required for the molecular assembly of iron-sulfur [Fe-S] clusters. Functional analysis of the predicted heavy metal resistance determinants demonstrated that their activity varies, depending on the host strain. This study provides the first molecular insight into the mobile DNA of Polaromonas spp. inhabiting polar glaciers. It has generated valuable data on the structure and properties of a pool of plasmids and highlighted their role in the biology of psychrotolerant Polaromonas strains and their adaptation to the environmental conditions of Arctic and Antarctic glaciers.